Recent advances in forensic anthropology: decomposition research - Daniel J. Wescott (Oxford University Press, 2018)
Decomposition research is still in its infancy, but significant advances have occurred within forensic anthropology and other disciplines in the past several decades. Decomposition research in forensic anthropology has primarily focused on estimating the postmortem interval (PMI), detecting clandestine remains, and interpreting the context of the scene. Additionally, while much of the work has focused on forensic-related questions, an interdisciplinary focus on the ecology of decomposition has also advanced our knowledge. The purpose of this article is to highlight some of the fundamental shifts that have occurred to advance decomposition research, such as the role of primary extrinsic factors, the application of decomposition research to the detection of clandestine remains and the estimation of the PMI in forensic anthropology casework. Future research in decomposition should focus on the collection of standardized data, the incorporation of ecological and evolutionary theory, more rigorous statistical analyses, examination of extended PMIs, greater emphasis on aquatic decomposition and interdisciplinary or transdisciplinary research, and the use of human cadavers to get forensically reliable data.